Influenza Hemagglutinin Protein Stability, Activation, and Pandemic Risk. Issue 10 (October 2018) - Russell, Charles J.; Hu, Meng; Okda, Faten A.
Abstract : For decades, hemagglutinin (HA) protein structure and its refolding mechanism have served as a paradigm for understanding protein-mediated membrane fusion. HA trimers are in a high-energy state and are functionally activated by low pH. Over the past decade, HA stability (or the pH at which irreversible conformational changes are triggered) has emerged as an important determinant in influenza virus host range, infectivity, transmissibility, and human pandemic potential. Here, we review HA protein structure, assays to measure its stability, measured HA stability values, residues and mutations that regulate its stability, the effect of HA stability on interspecies adaptation and transmissibility, and mechanistic insights into this process. Most importantly, HA stabilization appears to be necessary for adapting emerging influenza viruses to humans. Highlights: The structure and acid-induced activation mechanism of the influenza virus hemagglutin (HA) protein has served as a paradigm for protein-mediated membrane fusion over the past four decades. Recently, several laboratories have shown that, in order to adapt to humans and ferrets, influenza viruses need to acquire mutations that stabilize the HA protein. HA stability has been linked to pandemic potential and should be considered in surveillance, risk assessment tools, and prepandemic planning. In general, the preference for a stable or unstable HA protein varies by species. Thus, HA stability has been recently discovered as a novel trait associated with the ability of influenza viruses to cross species barriers. A knowledge of optimal HA activation pH values, and mutations affecting this property, may help investigators to generate enhanced vaccines and therapeutics.